Root rot increases the vulnerability of Norway spruce trees to Ips typographus infestation - Wahlman, Werna; Kasanen, R.; Lappalainen, L.; Honkaniemi, Juha (Elsevier, 2025)
Norway spruce (Picea abies) is one of the most economically important tree species in Northern and Central Europe. Root rot caused by Heterobasidion annosum s.l. and the European spruce bark beetle (Ips typographus) are major disturbance agents of Norway spruce and are expected to increasingly affect spruce-dominated forests as the climate warms. This study investigated the direct interaction between root rot and I. typographus, with the aim of examining whether root rot and the stress it causes to a tree increases the risk of subsequent bark beetle attack. In total, 442 Norway spruce trees from nine different mature, even-aged forest stands were studied. First, symptoms caused by I. typographus were evaluated before final felling from each tree based on visual assessments of crown and stem conditions. After the felling, the sample plots were relocated from the clearcut areas, and the stumps of sampled trees were reassessed for root rot. Exploratory analysis and binomial Generalized Linear Mixed Model (GLMM) were used to analyze relationships between explanatory variables and their effect to I. typographus infestation. The best predictors for I. typographus infestation at individual tree level were presence of root rot and to a lesser extent, tree diameter at breast height. Seventy-five percent of root rot-infected trees were also infested with I. typographus, and most of those trees were either dead or severely infested. Results suggest that root rot weakens trees, making them more vulnerable to subsequent I. typographus infestation, especially early in outbreaks when bark beetle population densities are low.
Keywords: Heterobasidion root rot; Ips typographus; European spruce bark beetle; Norway spruce; forest damages; disturbance interactions